Mapping Restorative Justice in Information and Electronic Transaction Criminal Regulation - Devi Triasari; Willy Naresta Hanum; Viddy Firmandiaz (Journal of Human Rights, Culture and Legal System, 2023)
The government has issued various policies to overcome overcapacity in prisons, but the important question that needs to be asked is whether these policies have restored the rights of victims of criminal acts of Information and Electronic Transactions. The method used in this study is a normative legal research method that examines secondary data. Data collection is carried out in the form of laws and regulations, reference books, and previous studies. The results of the research show that there is a need for the urgency of the application of restorative justice in criminal acts of Information and Electronic Transactions in Indonesia and what are the obstacles to the application of restorative justice in handling cases of criminal acts of Information and Electronic Transactions.